Evaluation of In Vitro-Derived Hop Plantlets, cv. Columbus and Magnum, as Potential Source of Bioactive Compounds - Leandra Leto; Claudia Favari; Anna Agosti; Lorenzo Del Vecchio; Andrea Di Fazio; Letizia Bresciani; Pedro Mena; Valeria Guarrasi; Martina Cirlini; Benedetta Chiancone (MDPI AG, 2024)
The demand for bioactive secondary metabolites of natural origin is increasing every day. Micropropagation could be a strategy to respond more quickly to market demands, regardless of seasonality. This research aims to evaluate in vitro-grown plants of two hop varieties, namely Columbus and Magnum, as a potential source of bioactive compounds. The extracts were characterized in terms of total phenolic content by a Folin-Ciocalteu assay and antioxidant capacity by DPPH•, ABTS+, and FRAP assays. The bioactive compound profile of the extracts from both varieties was determined by using UPLC-ESI-QqQ-MS/MS. The results confirmed richness in (poly)phenols and other secondary metabolites of the in vitro-grown hop plantlets. Thirty-two compounds belonging to the major families of phytochemicals characteristic of the species were identified, and twenty-six were quantified, mainly flavonoids, including xanthohumol and isoxanthohumol, phenolic acids, as well as α- and β-acids. This study confirms the validity of in vitro-derived hop plantlets as source of bioactive compounds to be used in the nutraceutical, pharmaceutical, and food industries.